2018
DOI: 10.1002/elan.201800072
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Determination of Sugar Probes Used for Gastrointestinal Permeability Test by Employing Nickel‐Copper Nanoalloy Embedded in Carbon Film Electrodes

Abstract: Co‐sputtered Ni/Cu nanoalloy embedded in carbon film electrodes were applied to an isocratic high performance liquid chromatography (HPLC) electrochemical detector to analyze urinary sugar probes used to assess gastrointestinal permeability. Electrode activity was easily controlled by varying the amounts of embedded nanoalloys without changing the Ni/Cu ratio. The high electrocatalytic activity of a nanoalloy makes it possible to achieve a limit of detection (LOD) of several tens of nM, which is one or two ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Overall, our selective electrodeposition method can fabricate Pt/Au, Pt/Pd, Pd/Au, Au/Pd, Ni/Au, and Ni/Pd heterodimers semiembedded in flat conductive C film. The cosputtering method can embed a wide variety of small (2–5 nm) metal nanoparticles in C film including Pt, , Pd, Au, Ir, Ni, Cu, Co, and Ni–Cu alloy , nanoparticles, with free control over the amount of embedded nanoparticles and the alloy composition. Therefore, a wide variety of metallic heterodimers could also be formed by the selective electrodeposition method.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Overall, our selective electrodeposition method can fabricate Pt/Au, Pt/Pd, Pd/Au, Au/Pd, Ni/Au, and Ni/Pd heterodimers semiembedded in flat conductive C film. The cosputtering method can embed a wide variety of small (2–5 nm) metal nanoparticles in C film including Pt, , Pd, Au, Ir, Ni, Cu, Co, and Ni–Cu alloy , nanoparticles, with free control over the amount of embedded nanoparticles and the alloy composition. Therefore, a wide variety of metallic heterodimers could also be formed by the selective electrodeposition method.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The obtained detection limits are about 1-2 orders of magnitude improved than those obtained with Au (by pulse amperometric detection) and Ni bulk electrodes, which is sufficient to detect diagnostic marker sugars in urine samples. 65…”
Section: Carbon Film Electrodes Embedded With Ni/cu Nanoalloymentioning
confidence: 99%
“…However, it was also found that NEPCSs provide an overall current response for all saccharides tested. Therefore, a pre-separation step is necessary if quantification of individual saccharides is required in terms of their application in food and environmental analysis, where they could serve as sensitive electrochemical detection systems [28][29][30][31]. ), uric acid (≥99%), and suspensions of monodisperse polystyrene beads with particle sizes of 200 or 500 nm were purchased from Sigma Aldrich (Prague, Czech Republic).…”
Section: Introductionmentioning
confidence: 99%